Neuroimmune mechanisms of stress: sex differences, developmental plasticity, and implications for pharmacotherapy of stress-related disease. (4th July 2015) - Deak, Terrence; Quinn, Matt; Cidlowski, John A.; Victoria, Nicole C.; Murphy, Anne Z.; Sheridan, John F.
Abstract: The last decade has witnessed profound growth in studies examining the role of fundamental neuroimmune processes as key mechanisms that might form a natural bridge between normal physiology and pathological outcomes. Rooted in core concepts from psychoneuroimmunology, this review utilizes a succinct, exemplar-driven approach of several model systems that contribute significantly to our knowledge of the mechanisms by which neuroimmune processes interact with stress physiology. Specifically, we review recent evidence showing that (i) stress challenges produce time-dependent and stressor-specific patterns of cytokine/chemokine expression in the CNS; (ii) inflammation-related genes exhibit unique expression profiles in males and females depending upon individual, cooperative or antagonistic interactions between steroid hormone receptors (estrogen and glucocorticoid receptors); (iii) adverse social experiences incurred through repeated social defeat engage a dynamic process of immune cell migration from the bone marrow to brain and prime neuroimmune function and (iv) early developmental exposure to an inflammatory stimulus (carageenin injection into the hindpaw) has a lasting influence on stress reactivity across the lifespan. As such, the present review provides a theoretical framework for understanding the role that neuroimmune mechanisms might play in stress plasticity and pathological outcomes, while at the same time pointing toward features of the individual (sex, developmental experience, stress history) that might ultimately be used for the development of personalized strategies for therapeutic intervention in stress-related pathologies.